2011
DOI: 10.1007/s13213-011-0211-z
|View full text |Cite
|
Sign up to set email alerts
|

Identification of multi-trait PGPR isolates and evaluating their potential as inoculants for wheat

Abstract: Development of an effective plant growth promoting rhizobacteria (PGPR) inoculant necessitates the presence of a diverse set of traits that can help its colonization of the rhizosphere and survival under varying environmental conditions. In our investigation, a set of 100 bacterial isolates from the rhizosphere of wheat plants were screened initially on the basis of a seed germination assay; ten bacterial isolates (AW1-AW10) were selected. These isolates were then tested in vitro for specific PGPR traits, such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
89
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(104 citation statements)
references
References 36 publications
(29 reference statements)
12
89
1
2
Order By: Relevance
“…1 and 2). According to Rana et al (2011), PGPR enhanced the uptake of N, P, and micronutrients in treated plants, which can partially explain our results.…”
Section: Micronutrients Display Different Concentration Patterns In Psupporting
confidence: 62%
“…1 and 2). According to Rana et al (2011), PGPR enhanced the uptake of N, P, and micronutrients in treated plants, which can partially explain our results.…”
Section: Micronutrients Display Different Concentration Patterns In Psupporting
confidence: 62%
“…(AW5) and Alcaligenes sp. (AW10) possess ACC deaminase activity (3.13 and 9.5 μm α-ketobutyrate/mg/h, respectively) [2]. In our study, the two isolates showed activity of 3.90×10 -6 μmol α-keto butyrate/ mg protein/ h and 2.92×10 -6 μmol α-keto butyrate/mg protein/h by isolate UHI(II)7 and CHII(II)K7.…”
Section: Figuresupporting
confidence: 45%
“…They offer an attractive way for sustainable agricultural system by reducing the use of chemical fertilizers [1][2][3]. Most of the world population still relies mainly on herbal products and medicines for health care [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…P-solubilization was further determined using the Mo-blue method (Chen et al 2006). Indoleacetic acid (IAA) and siderophore production were measured using Salkowski reagents and CAS medium, respectively (Rana et al 2011).…”
Section: Microorganismsmentioning
confidence: 99%